2008
DOI: 10.1002/jbt.20237
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin, an antioxidant flavonoid, prevents acrylonitrile‐induced oxidative stress in rat brain

Abstract: Acrylonitrile (ACN) is a volatile, toxic liquid used as a monomer in the manufacture of synthetic rubber, styrene plastics, acrylic fiber, and adhesives. ACN is a potent neurotoxin. A role for free radical mediated lipid peroxidation in the toxicity of ACN has been suggested. We examined the ability of hesperidin, an antioxidant flavonoid, to attenuate ACN-induced alterations in lipid peroxidation in rat brains. The daily oral administration of ACN to male albino rats in a dose of 50 mg/kg bwt for a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…It has reported that HES treatment increased SOD, CAT and GSH-Px activities and reduced the tissue damage caused by oxidative stress-induced ischemia and I/R 75 . It was suggested that HES has positive effects on SOD, CAT and GSH-Px activities and has protective effects against oxidative stress in rat brain 76 . In another study, it has been demonstrated that EA enhanced increased tissue SOD, CAT and GSH-Px activities 77 .…”
Section: Resultsmentioning
confidence: 99%
“…It has reported that HES treatment increased SOD, CAT and GSH-Px activities and reduced the tissue damage caused by oxidative stress-induced ischemia and I/R 75 . It was suggested that HES has positive effects on SOD, CAT and GSH-Px activities and has protective effects against oxidative stress in rat brain 76 . In another study, it has been demonstrated that EA enhanced increased tissue SOD, CAT and GSH-Px activities 77 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to off er neuroprotection (Heff ner and Repine 1989), to improve oxidative stress in carbon tetrachloride-treated rats (Tirkey et al 2005), to control pathophysiological disturbances of brain excitability in drug abuse, migraine and epilepsy (Dimpfel 2006) and to protect against cerebral ischemia reperfusion injury-induced alterations (Gaur et al 2011). Its co-administration with acrylonitrile attenuates oxidative stress (El Sayed et al 2008). Moreover, HES was reported to enhance immune competence, and decrease irradiationinduced infl ammation (Lee et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Our findings offer new evidence that natural and chemically synthesized antioxidants provide neuroprotection against AN-induced neurotoxicity (Benz et al, 1990;Carrera et al, 2007;Esmat et al, 2007;El-Sayed et al, 2008;Guangwei et al, 2010;Mahalakshmi et al, 2003). Nonetheless, the efficacy of antioxidants in attenuating AN-induced astrocytic damage is dependent both on the timing and dosage of administration (Carrera et al, 2007;Gitika et al, 2006).…”
Section: Discussionmentioning
confidence: 78%